2001
DOI: 10.1021/es001607i
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate and Arsenite Removal by Zerovalent Iron:  Kinetics, Redox Transformation, and Implications for in Situ Groundwater Remediation

Abstract: Batch tests were performed utilizing four zerovalent iron (Fe0) filings (Fisher, Peerless, Master Builders, and Aldrich) to remove As(V) and As(III) from water. One gram of metal was reacted headspace-free at 23 degrees C for up to 5 days in the dark with 41.5 mL of 2 mg L(-1) As(V), or As(III) or As(V) + As(III) (1:1) in 0.01 M NaCl. Arsenic removal on a mass basis followed the order: Fisher > Peerless Master Builders > Aldrich; whereas, on a surface area basis the order became: Fisher > Aldrich > Peerless Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
240
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(278 citation statements)
references
References 43 publications
31
240
1
6
Order By: Relevance
“…As(III) and As(V) removals by iron oxides normally behave differently at different pH (Edwards, 1994;Hering et al, 1996;Bose and Sharma, 2002). Su and Puls (2001) have reported that As(III) shows greater removal than As(V), and mixture of As(V) and As(III) showed intermediate removal by iron oxides. It has been reported that pH is an important operating factor influencing the performance of electrocoagulation process (Chen et al, 2000).…”
Section: Effect Of Phmentioning
confidence: 99%
See 3 more Smart Citations
“…As(III) and As(V) removals by iron oxides normally behave differently at different pH (Edwards, 1994;Hering et al, 1996;Bose and Sharma, 2002). Su and Puls (2001) have reported that As(III) shows greater removal than As(V), and mixture of As(V) and As(III) showed intermediate removal by iron oxides. It has been reported that pH is an important operating factor influencing the performance of electrocoagulation process (Chen et al, 2000).…”
Section: Effect Of Phmentioning
confidence: 99%
“…They reported that As(III) and As(V) normally behave differently in terms of pH on the adsorption on hydrous ferric oxides. Some investigators have reported that favorable adsorption of As(V) on to hydrous ferric oxides at pH < 7 (Farrell et al, 2001;Su and Puls, 2001), while others have reported more favorable adsorption of As(III) at pH > 7 (Jain et al, 1999) and equal amounts of As(V) and As(III) adsorption below pH 7 (Su and Puls, 2001). Therefore the adsorption capacities of As(III) and As(V) in electrocoagulation and chemical coagulation were investigated.…”
Section: Electrocoagulation (Ec) Vs Chemical Coagulation (Cc)mentioning
confidence: 99%
See 2 more Smart Citations
“…The zero valent iron (ZVI) permeable reactive barrier (PRB) is an in-situ technology for the remediation of heavy metals, chlorinated hydrocarbons and radioactive materials in groundwater (Gillham and Ohannesin, 1994;Gu et al, 1998;Su and Puls, 2001;Agrawal et al, 2002). Although encouraging treatment efficiency has been documented (Gu et al, 1998;Morrison et al, 2001;Su and Puls, 2003), reactions between ZVI and groundwater constituents causing ZVI corrosion and subsequent secondary mineral precipitation contribute to long term performance reduction of ZVI PRBs (Liang et al, 2003;Slater and Binley, 2003;Wilkin et al, 2003;Jin Suk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%